Anti-externalism - Mendola, Joseph (Oxford : Oxford University Press, 2008)
Internalism about the mind is the view that your thoughts and sensations are constituted by conditions inside your skin. Externalism denies this, and over the past 30 years has become the dominant view in philosophy of mind. Joseph Mendola argues that the externalist theories are false and develops a viable internalist alternative.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Externalism (Philosophy of mind)